2022
DOI: 10.1002/hep.32479
|View full text |Cite
|
Sign up to set email alerts
|

Circulating HBV RNA: From biology to clinical applications

Abstract: Chronic HBV infection can hardly be cured due to the persistence of an intrahepatic pool of viral covalently closed circular DNA (cccDNA) transcription template, which is refractory to current antivirals. The direct analyses of cccDNA quantity and transcriptional activity require an invasive biopsy. Recently, circulating HBV RNA has been identified as a promising noninvasive surrogate marker of cccDNA and can be used for monitoring disease progression and predicting prognosis of patients with chronic HBV infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Moreover, in animal models, like immunocompromised HBV‐transgenic mice or HBV‐infected humanized chimeric mice, only very low levels of naked capsids were detectable (Hong et al., 2021). Although the physiological relevance of naked capsids must be confirmed beyond doubt, they may carry HBV‐specific DNA and RNA species (Deng et al., 2022; Liu et al., 2019) and have been shown to be competent for clathrin‐mediated endocytosis (Cooper & Shaul, 2006). Accordingly, their uptake may enhance transmission of HBV genomes.…”
Section: Hbv and Subunit Particlesmentioning
confidence: 99%
“…Moreover, in animal models, like immunocompromised HBV‐transgenic mice or HBV‐infected humanized chimeric mice, only very low levels of naked capsids were detectable (Hong et al., 2021). Although the physiological relevance of naked capsids must be confirmed beyond doubt, they may carry HBV‐specific DNA and RNA species (Deng et al., 2022; Liu et al., 2019) and have been shown to be competent for clathrin‐mediated endocytosis (Cooper & Shaul, 2006). Accordingly, their uptake may enhance transmission of HBV genomes.…”
Section: Hbv and Subunit Particlesmentioning
confidence: 99%
“…First, we confirmed the circulation of enveloped HBV-RNA containing particles in plasmas [ 15 ]. These particles were present in lower fractions together with Dane particles, both in velocity and density gradients.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to inhibiting the production of HBV virions, we show that GS-SBA-1, but not TAF, can also prevent the production of extracellular HBV RNA-containing particles. We and others have demonstrated that circulating HBV RNA particles, which can contain various HBV RNAs, including HBx transcripts, are present in cell culture-derived virus preparations and the serum of CHB patients ( 38 , 43 , 44 ). Circulating HBV RNAs have been linked with an increased risk of HCC ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that HBV RNAs may directly promote HCC development through interactions with host oncogenes and/or increased intrahepatic inflammation and fibrosis ( 47 , 48 ). HBV DNA integration, which is considered to play a role in HCC development, may also lead to the production of circulating HBV RNAs ( 43 ). Additionally, HBV RNA transcripts potentially could directly express HBx protein upon infection in a cccDNA-independent manner to support cccDNA transcription by antagonizing host restriction factors such as the SMC5/6 complex ( 38 , 44 ).…”
Section: Discussionmentioning
confidence: 99%